Creating a Modern “Zone of Genocide”: The Impact of Nation- and State-Formation on Eastern Anatolia, 1878–1923 - Levene, Mark (Holocaust and genocide studies, 1998)
The persistence of genocide or near-genocidal incidents from the 1890s through the 1990s, committed by Ottoman and successor Turkish and Iraqi states against Armenian, Kurdish, Assyrian, and Pontic Greek communities in Eastern Anatolia, is striking. This article traces the origins of these incidents by examining emerging Armenian, Turkish, and Kurdish national movements and their competition for the region's resources. It argues that the creation of this “zone of genocide” in Eastern Anatolia cannot be understood in isolation, but only in light of the role played by the Great Powers in the emergence of a Western-led international system.